The Effects of Digital Project-based Learning on EFL Students’ Pronunciation - Phokaew, Phinyarat; Yimwilai, Supaporn; Srichote, Patipat (Manutsat Paritat: Journal of Humanities, 2025)
This research study examined the impact of integrating technology into project-based learning, specifically digital project-based learning (DPBL), in an English as a Foreign Language (EFL) classroom. The primary objective was to explore the effects of DPBL on students’ pronunciation, particularly focusing on final sounds. Additionally, the study sought to gather students’ opinions about their experience with DPBL. The participants comprised 35 ninth-grade students from a public school, selected through a purposive sampling method. The instruments employed included lesson plans, a task, a pronunciation test, and a questionnaire. Quantitative data were analyzed using mean scores, standard deviations, and a dependent samples t-test, while qualitative data were assessed through content analysis. The results highlighted the promising potential of applying DPBL in the EFL classroom. Specifically, the mean score of the posttest (40.80) was significantly higher than that of the pretest (16.54) at the 0.5 level. Furthermore, all students expressed positive opinions about this teaching method. This study suggests that project-based learning, coupled with technology, can enhance the language acquisition process for EFL students.